1997
DOI: 10.1046/j.1464-410x.1997.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pH on urinary ionized [Ca+]: differences between urinary tract stone formers and normal subjects

Abstract: Objective To assess the role of pH in determining the formers, at 7.67 (0.62) and 7.21 (0.54), respectively, and nearer to their voided pH of 5.92 (0.70) and 6.26 solubility of Ca2+ in urine from normal subjects and stone formers and to determine the conditions which (0.71), respectively. The lower pH n in stone-formers could not be explained by altered concentrations cause the formation of crystalline products. Materials and methods Urine, collected from normal or binding properties of Ca2+-binding ligands. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
(11 reference statements)
0
9
0
1
Order By: Relevance
“…In a previous study it was shown that pH n in urine collected from urinary tract stone‐formers was significantly more acid than that from normal subjects [ 10]. The shift in pH n was strongly dependent on the total [Ca] as well as ionized [Ca 2+ ] at a standard pH; the pH n was lower at higher Ca levels in the stone‐forming group.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In a previous study it was shown that pH n in urine collected from urinary tract stone‐formers was significantly more acid than that from normal subjects [ 10]. The shift in pH n was strongly dependent on the total [Ca] as well as ionized [Ca 2+ ] at a standard pH; the pH n was lower at higher Ca levels in the stone‐forming group.…”
Section: Discussionmentioning
confidence: 93%
“…The voided urinary pH (pH v ) was measured in a urine sample drawn into a glass syringe within 45 s of micturition, to minimize CO 2 loss [ 10]. Urine was submitted for routine bacteriological culture and to test for urease activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas urinary pH and Ca 2+ are inversely related [6, 7], both systemic and urinary acidosis may inhibit renal citrate excretion if citrate reabsorption and metabolism in the proximal tubule become up-regulated in order to counteract imbalanced acid–base status [1, 8]. …”
Section: Introductionmentioning
confidence: 99%